2019
DOI: 10.1186/s12893-018-0463-7
|View full text |Cite
|
Sign up to set email alerts
|

Altemeier’s procedure for complete rectal prolapse; outcome and function in 43 consecutive female patients

Abstract: BackgroundThe aim of this retrospective study was to evaluate morbidity, mortality, postoperative function and recurrences in patients treated by Altemeier’s rectosigmoidectomy for complete rectal prolapse in a referral center for pelvic floor functional disorders.MethodsPeri-operative data on 43 consecutive female patients were reviewed. At follow-up any change in pelvic floor function and recurrences were determined. Thirty four patients were assessed at a median interval of 49 (2–135) months, six being dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 36 publications
3
46
0
4
Order By: Relevance
“…Therefore, we performed levatorplasty for the patient. Although increased daily frequency of stools or fecal incontinence has been reported as postoperative complications of the Altemeier procedure[ 17 ], these symptoms were not observed in our patient, partly because she managed her mental illness and recovered from spice abuse and laxative addiction after surgery.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, we performed levatorplasty for the patient. Although increased daily frequency of stools or fecal incontinence has been reported as postoperative complications of the Altemeier procedure[ 17 ], these symptoms were not observed in our patient, partly because she managed her mental illness and recovered from spice abuse and laxative addiction after surgery.…”
Section: Discussionmentioning
confidence: 56%
“…recovery and reconstruction of the intestine, cutting and anastomosis of the ureteral intestine). We have compared our method with other approached in several publications 15 , 16 . One previous study 15 reported that completely intracorporeal robotic ileal ureteric replacement had longer operative time (328 min), more estimated blood loss (100 ml) and longer length of the ileal substitute (20.4 cm), which was worse results than our method.…”
Section: Discussionmentioning
confidence: 99%
“…Complete mesocolic excision for colon cancer has been shown to provide superior oncological outcomes and better survival advantage compared to standard resection [1][2][3]. Laparoscopic complete mesocolic excision for transverse colon cancer is technically challenging and carries the risk of serious complications.…”
Section: Dear Editormentioning
confidence: 99%
“…Robotic technology has been developed to reduce the technical limitations of laparoscopy. The robotic platform provides further advantages including a greater range of motions, added dexterity and precision with extended operative reach in multiple quadrants [1,[2][3][4][5][6].…”
Section: Dear Editormentioning
confidence: 99%